The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11999-012-2634-7
|View full text |Cite
|
Sign up to set email alerts
|

Is Further Treatment Necessary for Patellar Crepitus After Total Knee Arthroplasty?

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…59 Furthermore, there are more options for the attainment of proper patellar tracking, including using a patella friendly femoral prosthesis 59 and performing appropriate patelloplasty. 39 Lateral retinacular release may stimulate scar tissue formation up to the synovial lining overlying the top of the femoral component and the peripatellar soft tissue. As the detailed mechanism of the association between PCC and lateral retinacular release remains unknown, the indications for lateral release should be considered carefully.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…59 Furthermore, there are more options for the attainment of proper patellar tracking, including using a patella friendly femoral prosthesis 59 and performing appropriate patelloplasty. 39 Lateral retinacular release may stimulate scar tissue formation up to the synovial lining overlying the top of the femoral component and the peripatellar soft tissue. As the detailed mechanism of the association between PCC and lateral retinacular release remains unknown, the indications for lateral release should be considered carefully.…”
Section: Discussionmentioning
confidence: 99%
“…There were also other factors for which the data from different studies could not be pooled due to inconsistent data forms, a broad range of definitions, or the data being reported only in a single study. The potential risk factors for PCC that were not included in the pooled analyses due to high heterogeneity and inconsistent data forms included patellar thickness, 10,29,52 postoperative joint line, 29,38,40 posterior femoral condylar offset, 10,29,39,52 patellar tendon length, 10,39,52 Z distance, 38,40 "P distance" (position of the proximal pole of the patella with reference to the distal end of the femoral prosthesis), 38,40 lateral displacement of the patella, 38,40 and preoperative knee flexion. 10,29 We were also unable to pool the data on the patellar, femoral, and tibial component sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The etiology and pathogenesis of AKP after TKA remain unclear, although several contributing factors have been identified, like patellar instability and maltracking [4,5]. Patellar crepitus is defined as a grinding sensation in the region of the distal quadriceps tendon over the patella when the knee is brought from flexion to extension, and secondary to fibrosynovial proliferation on the posterior aspect of the distal quadriceps tendon [6]. A previous study reported that up to one-third of patients who underwent TKA experienced mild to moderate AKP at the 1-year follow-up [7].…”
Section: Introductionmentioning
confidence: 99%